Analysis of the Feasibility of Eco-enzyme Liquid Organic Fertilizer (POC) Business in Sumber Jaya Farmer Group, Puring District, Kebumen Regency - Fatmawati, Nurlaila; Setyawan, Heri; Aji, Wandha Atmaka (Akademi Komunitas Perkebunan Yogyakarta, 2024)
This research was carried out in Sidobunder Village, Puring District, Kebumen Regency. This research was carried out from December 2023 to January 2024. This study aims to analyze the income and feasibility of the eco-enzyme liquid organic fertilizer business in the Sumber Jaya Farmers Group, Puring District, Kebumen Regency from a financial perspective through the calculation of Break Even Point (BEP), Benefit Cost Ratio (BCR) and Revenue Cost Ratio (R/C). The method used is a survey through observation and direct interviews. The determination of farmers as research respondents was by Purposive Sampling, respondents were taken from 30 farmer members in the Sumber Jaya Farmers Group. This location was chosen because this village is one of the production places for eco-enzyme liquid fertilizers and has the potential for the development of eco-enzyme liquid fertilizers. The data was analyzed using an income analysis model and a financial feasibility analysis. Then the data is tabulated and processed mathematically, through addition, and the averages and percentages are then descriptively described. The results of this study show that the income/year in the Sumber Jaya Farmers Group, Puring District, Kebumen Regency is Rp. 14,447,834 or income/month is Rp. 1,203,986. Based on the feasibility of the eco-enzyme liquid organic fertilizer business in Sumber Jaya Farmers Group, Puring District, Kebumen Regency, it is feasible to be developed financially because of the BEP value of 14,400 bottles with a minimum of 142 bottles. BEP is priced at IDR 10,000 with a minimum price of IDR 8,997/bottle, and an R/C value of 1.11 means that the R/C value is feasible.